'Show me the compassion!' Changing the organisational mind within construction industry. (2018) - Barrett, Dirk; Khalfan, Malik M.A.
The construction industry is highly adversarial, with multiple parties each with their own agenda and needs drowning in the sea of uncertainty. This paper, through an extended literature review, introduced a theoretical model of how the organisational mind can influence organisational culture, with implications for all aspects of the construction industry. Finding new and innovative ways of building is going to take the shared experience of all the minds within the 'organisation'. The outcomes of the research show that certain mental attributes are trained as a result of practicing self-compassion, compassion, empathy, perspective and mindfulness. Those practices for example and others potentially enable the culture within the organisation to flow through imitative learning, having a positive effect on stakeholders who interact.